Frailty and adverse outcomes: impact of multiple bed moves for older inpatients. (3rd October 2016) - Ranasinghe, Champa; Fleury, Aisling; Peel, Nancye M.; Hubbard, Ruth E.
ABSTRACT: Background: A consequence of pressure on hospitals to accommodate care needs of older patients is "boarding" or out-lying from their home ward. This may have greater adverse effects on older inpatients who are frail. Methods: A retrospective matched cohort study was conducted in an outer metropolitan general hospital. Randomly selected patients hospitalized between July 2012 and June 2013 under the care of an Older Person Evaluation Review and Assessment (OPERA) team (n = 300) were age and sex matched with patients under the care of general physicians (n = 300). Frequency of boarding and number of bed moves were recorded for all patients. For patients who had three or more moves, adverse outcomes were compared between the two groups. Results: A higher proportion of OPERA patients (n = 143; 47.7%) were out-lied from medical wards compared with 94 (31.3%) General Medicine patients ( p < 0.001). Three or more bed moves were recorded for 67 (22.3%) OPERA and 24 (8%) General Medicine patients ( p < 0.001). Of those with multiple moves, OPERA patients were more likely to have pre-morbid cognitive impairment ( p = 0.005), to be moderately to severely frail ( p = 0.016) and to suffer acute delirium and falls during admission ( p = 0.03), compared with General Medicine patients. OPERA patients were also more at risk of adverse outcomes such as increased dependence, discharge to residential care or death ( p = 0.023). Conclusion: Compared with age- and sex-matched General Medicine patients, OPERA patients were more likely to undergo multiple bed moves and out-lying, which may have contributed to negative outcomes for these patients.